2017
DOI: 10.3847/1538-4357/aa96ac
|View full text |Cite
|
Sign up to set email alerts
|

On Nulling, Drifting, and Their Interactions in PSRs J1741–0840 and J1840–0840

Abstract: We report detailed investigation of nulling and drifting behavior of two pulsars PSRs J1741−0840 and J1840−0840 observed from the Giant Meterwave Radio Telescope at 625 MHz. PSR J1741−0840 was found to show nulling fraction (NF) of around 30±5% while PSR J1840−0840 was shown to have NF of around 50±6%. We measured drifting behavior from different profile components in PSR J1840−0840 for the first time with the leading component showing drifting with 13.5±0.7 periods while the weak trailing component showed dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 55 publications
3
22
0
Order By: Relevance
“…Another similar phenomenon is periodic nulling that has been widely reported in many pulsars (Herfindal & Rankin 2007, 2009Rankin & Wright 2008;Rankin et al 2013;Gajjar et al 2014Gajjar et al , 2017Basu et al 2017). The periodicities of the amplitude modulation are very similar to periodic nulling, causing Basu et al (2017) to propose that they both may have a common origin.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Another similar phenomenon is periodic nulling that has been widely reported in many pulsars (Herfindal & Rankin 2007, 2009Rankin & Wright 2008;Rankin et al 2013;Gajjar et al 2014Gajjar et al , 2017Basu et al 2017). The periodicities of the amplitude modulation are very similar to periodic nulling, causing Basu et al (2017) to propose that they both may have a common origin.…”
Section: Discussionsupporting
confidence: 52%
“…However, Basu et al (2017) found that the missing line of sight model did not adequately explain the periodic nulling observed in many pulsars, particularly in pulsars with core components. Additionally, because of lack of phase memory and partial nulls, the missing line of sight model is probably not applicable to the quasi-periodic feature seen in PSR J1741−0840 (Gajjar et al 2017). For the periodic Q-mode modulation of PSR J1825−0935 reported in this paper, the IP and the MP switch between a strong state and a weak state periodically.…”
Section: Discussionmentioning
confidence: 82%
“…A second possibility is that the nulling events occur when the leading component is at (or near) its weakest point in the modulation cycle. This is similar to that observed by Gajjar et al (2017) for PSR J1840−0840 which consistently enters the null state at the end of a drift-band in one of its profile components. For PSR J1926−0652 we can not make such a definitive statement as we do see clear emission in the leading component in the last active pulse for Burst 3.…”
Section: The Subpulse Drifting and Nulling Phenomenasupporting
confidence: 87%
“…Periodic nulling has been reported in some pulsars (Herfindal & Rankin 2007, 2009Rankin & Wright 2008;Rankin et al 2013;Gajjar et al 2014Gajjar et al , 2017Basu et al 2017;Basu & Mitra 2018;Basu et al 2019b;Basu & Mitra 2019). Observed periodicities in the amplitude modulation of some components of some pulsars are very similar to periodic nulling, and therefore Basu et al (2017) suggested that they have a common origin.…”
Section: Discussionmentioning
confidence: 91%
“…However, Basu et al (2017) found that the missing LOS model did not adequately explain the periodic nulling observed in pulsars with core components. Additionally, (Gajjar et al 2017) found that the missing LOS model is probably not applicable to the quasi-periodic changes between the null and burst states seen in PSR J1741−0840. For the periodic amplitude modulation of PSR J1048−5832 reported in this paper, the probable central core component and the trailing conal component switch between a strong mode and a weak mode periodically.…”
Section: Discussionmentioning
confidence: 99%